Bahasa Indonesia . - Nastangin, Nastangin Nastangin; Latifa, Soraya Al; Huda, Muhammad Chairul (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
This study aims to determine the role of the mediator at the Islamic Legal Consultation and Assistance Institute (LKBHI) IAIN Salatiga in handling divorce cases. This research is a qualitative research. Researchers go directly to the field (fieldwork research) to explore comprehensive data on research subjects, namely LKBHI IAIN Salatiga. The method of collecting data in this research was observation and in-depth interviews (in depth interviews). The analysis used is deductive-inductive. The theory in this study uses the theory of ishlah (peace). The results of this research are first, the mediator of LKBHI IAIN Salatiga experienced several obstacles in handling divorce, that the complexity of the problems of the litigants, so that in mediation it became more difficult to reconcile even though some were successful and some were not. Second, the implementation of mediation according to the rules in PERMA No. 1 of 2016. Third, the role of the mediator is basically in accordance with the theory of ishlah (peace). The novelty of this research is the discovery of efforts that can be taken by mediators in making efforts to making peace between the litigants. The mediator can take several approaches, namely providing religious spirituality values, the importance of children's future, nostalgia for the days of marriage, framing problems and caucuses.